Jeersanidhi Memorial Lecture â€“ Smuts of wheat: A review - BASANT RAM* and K.P. SINGH - K.P. SINGH, BASANT RAM* and (Indian Phytopathology, 2004)
Amongst the cultivated plants subjected to serious smut diseases, the cereals are the most common. In India, loose smut and flag smut are the important diseases attacking wheat crop. Loose smut is distributed throughout the country but appears to be more in North than in the South. On the other hand, flag smut is important only in certain localized regions of the country. Smut fungi belonging to order Ustilaginales are parasites both on monocots and dicots. Since they impart sooty appearance due to production of black spore mass they are generally described as smut fungi. The mycelium of these fungi is parasitic dikaryotic and quite often intercellular in the host plant, may be systemic or localized. Ustilaginales as a group do not possess orgainsed sex- organs but dikaryotization is brought about by the fusion of mycelial hyphae or by fusion of basidiospores or sporidia. Chlamydospores, the reproductive structures have been designated variably. Apparently Prevost (1807) recorded existence of these â€œbodiesâ€ in Tilletia caries and called them as â€œgemmaeâ€. Since then they have been designated under different names such as â€œresting sporesâ€, â€œchlamydosporesâ€. â€œteleutosporesâ€, or â€œaeciosporesâ€. The â€œchlamydosporesâ€ was probably used for the first time by Brefeld (Mc Alpine, 1910) but most of the workers do no accept this terminology now and in recent years use of term â€œTeliospresâ€ is in vogue. Brief historical account of smut fungi like rusts, reference to â€œsmutâ€, â€œmildewsâ€ have been made in ancient books but is rather impossible to distinguish clearly the record of smut from other diseases.